2017
DOI: 10.7150/jca.17416
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for cervical intraepithelial neoplasia and cervical cancer in Chinese women: large study in Jiexiu, Shanxi Province, China

Abstract: We aimed to investigate the risk factors for cervical intraepithelial neoplasia (CIN) in Jiexiu, Shanxi Province, China. Twenty thousand eligible married women (age: 18-65 years) were administered with a questionnaire on potential risk factors for CIN and underwent liquid based Pap test. All women with abnormal cytological results underwent colposcopy with biopsy. Based on the biopsy pathology results, women were then assigned to either study group (with CIN) or control group (negative for histological results… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
50
1
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 28 publications
2
50
1
1
Order By: Relevance
“…Atypical squamous cells of undetermined significance and above were considered as TCT positive. All cases with atypical squamous cells of undetermined significance and above and 10% of cases with the negative results were further reviewed blindly by a senior cytopathology physician for quality control …”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…Atypical squamous cells of undetermined significance and above were considered as TCT positive. All cases with atypical squamous cells of undetermined significance and above and 10% of cases with the negative results were further reviewed blindly by a senior cytopathology physician for quality control …”
Section: Methodsmentioning
confidence: 99%
“…If the diagnoses were discordant between the two pathologists, the cases would be reviewed by the third senior pathologist. The three pathologists would review the cases together to arrive a consensus diagnosis for some difficult or equivocal cases . In addition, we performed immunohistochemical detection of p16 and Ki‐67 to assist the pathological diagnosis.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Latest cervical cancer statistical studies have shown that more than 85% of cervical cancer patient in Shanxi Province had never received proper screening and presented at late stage. As a result, the incidence and mortality of cervical cancer women living in Shanxi Province are 10-fold higher than that of other regions in China [9,10] . To date, little if any information is available concerning cervical cancer screening performance and diagnostic yield in this region [9][10][11][12] .…”
Section: Introductionmentioning
confidence: 99%